Aquaman the Movie, Through the Lens of Feminists - Arunrangsiwed, Proud; Seedoung, Muntira (Journal of Applied Informatics and Technology, 2020)
The objective of the current article is to analyze the movie, Aquaman (2018 film), through feminism and social progressivism. The negative light shown in this film is that most characters believed in patriarchy, even for the main female protagonist, Mera. The power was transferred from men to men. The traditional role of female characters is just to be a wife and a mother. Minorities or unattractive races in this film were negatively stereotyped with poor personality and attribution. However, this film also consists of positive light for feminism. Mera, as the main female character, was with leadership, thinking skills, negotiation skills, and ability to make a decision. Her role could be read as active and subjective role of woman which are the major part of women’s empowerment. Moreover, this film also distinguishes the role of male heroes and villains that heroes would accept the advice of women, but the villain would use his power to oppress women. This helps teach male audiences to respect women and teach them the gender equality. The authors of this paper suggested that film audiences might be able to learn the equality and empowerment through non-superhero films better, because people could imitate prosocial behaviors from the media character with a similar attribute than from superhero characters. The authors expect Media Art and Communication Art students to study this paper in order to produce prosocial media in their future careers.